[A successful transplant begins with organ preservation] - Maathuis, M; Moers, C; Leuvenink, H; Ploeg, R (2008)
Organ preservation is a critical link in the chain of donation and transplantation and has a significant effect on post-transplant graft function and graft survival. Clinically, the most widely used form of preservation is static cold storage, which is based on the reduction of cellular metabolism by hypothermia. Although static cold storage is simple and effective, it is questionable whether it still meets present day requirements. Due to the persistent shortage of donors, increasing numbers of organs are being accepted from older and non-heart-beating donors. Organs from such donors may benefit from a more dynamic method of preservation: hypothermic machine perfusion.